Respuesta :

Answer:

A

Step-by-step explanation:

The explicit formula for a geometric sequence is

[tex]a_{n}[/tex] = a₁[tex](r)^{n-1}[/tex]

where a₁ is the first term and r the common ratio

Given the explicit formula

[tex]a_{n}[/tex] = 6[tex](-\frac{1}{4}) ^{n-1}[/tex]

where a₁ = 6 and r = - [tex]\frac{1}{4}[/tex]

A recursive formula allows any term in the sequence to be found by multiplying the previous term by r , thus

[tex]a_{n}[/tex] = [tex]a_{n-1}[/tex] (- [tex]\frac{1}{4})[/tex] with a₁ = 6 → A

Answer:

Step-by-step explanation: